IMPLEMENTASI PENILAIAN SIKAP PADA KURIKULUM 2013 MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI PADA JENJANG SD (Pengembangan Mata Diklat Penilaian hasil Pembelajaran Bagi Diklat Guru PAI SD) - Miftahusroyudin, Moh (Balai Diklat Keagamaan Surabaya, 2017)
This article presents assessment techniques attitude domainbased on the curriculum 2013, especially the subjects of IslamicReligious Education and moral value (PAI BP) elementary level. Thisdue to the demands i n assessment implementation amongattitude, knowledge and skill domains must be in a balance. In 2013,four elements of the National Education Standards 1) GraduateCompetency Standards, 2) Content Standards, 3) ProcessStandards, and 4) Evaluation Standards were revised. Assessment isan effort to collect and process the data of the learning process todetermine the level of achievement of the competence of thelearners as the basis of the follow-up decision of an educator. Whilethe attitude assessment is an assessment conducted by theteacher to measure the l evel of attai nment of atti tudinalcompetencies of learners that include aspects of receiving or payingattention, responding, assessing or appreciating, organizing andmanaging,. There are 3 ways to assess the domain of attitude that isthrough observation, sel f-assessment, and among friends.Observations are conducted during the process and outside thelearning process, while self-assessment and between friends is doneat least once a semester. Many of the difficulties experienced byteachers in the implementation ranging from the preparation ofrubric, implementation and the final processing technique.